2017
DOI: 10.1007/s40259-017-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Switching from Innovator Rituximab to Biosimilar CT-P10 Compared with Continued Treatment with CT-P10: Results of a 56-Week Open-Label Study in Patients with Rheumatoid Arthritis

Abstract: BackgroundCT-P10 is a biosimilar candidate of innovator rituximab (RTX) that demonstrated a comparable clinical profile to RTX in a phase I randomized controlled trial (RCT) in rheumatoid arthritis (RA) (ClinicalTrials.gov identifier: NCT01534884).ObjectiveThis open-label extension (OLE) study (NCT01873443) compared the efficacy and safety of CT-P10 in patients with RA who received CT-P10 from the outset (i.e., from the start of the RCT and also in the OLE; ‘maintenance group’) with those who received RTX duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 19 publications
(32 reference statements)
2
29
0
Order By: Relevance
“…Of the 23 clinical, non-medical switching studies (Table 1) [53, 55, 56, 60, 61, 69, 70, 7375, 81, 82, 8486, 91–99, 101104], 22 reported data on main efficacy parameters in switched versus non-switched or pre-switch versus post-switch groups. The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 23 clinical, non-medical switching studies (Table 1) [53, 55, 56, 60, 61, 69, 70, 7375, 81, 82, 8486, 91–99, 101104], 22 reported data on main efficacy parameters in switched versus non-switched or pre-switch versus post-switch groups. The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
“…The originator biologics/biosimilars assessed were infliximab (six studies [53, 55, 56, 61, 69, 70, 73]), erythropoietin-stimulating agents (ESAs) (four studies [74, 75, 81, 82]), filgrastim [9395] (three studies), insulin [8486], adalimumab [96–98], rituximab [60, 99] and etanercept [101103] (two studies each), and genotropin [83, 92] and follicle stimulating hormone [104] (one study each).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations